Efficacy of a Comprehensive Rehabilitation Program including Interactive Balance Therapy with Biofeedback and Hydrokinesitherapy in Reducing Body Weight and Changing of the Body Composition in Patients with Obesity - Valeria A. Vasileva; Larisa A. Marchenkova (Ministry of Health of the Russian Federation. National Medical Research Center of Rehabilitation and Balneology, 2023)
The problem of overweight (obesity) is steadily increasing.Aim. To evaluate the effectiveness of a new comprehensive rehabilitation program on the dynamics of weight and body compositionindicators using different methods after the rehabilitation stage and long-term results.Material and methods. Men and women aged 40 to 65 years with a body mass index ≥ 30 kg/m2 were included in the study. Thepatients were further divided into two groups by simple randomisation. Both groups underwent two weeks of medical rehabilitationon a low-calorie diet. The patients of the main group (group 1) received 4 methods of therapeutic physical exercises. Patients in thecomparison group (group 2) were treated only with aerobic exercise and therapeutic gymnastics. A dynamic observation was carriedout immediately after the course, after 3 and 6 months.Results and discussion. According to the data obtained, there was a significant reduction in body weight in both groups aftercompletion of the treatment phase, p=0.0001. There was a significant reduction in abdominal fat thickness after 14 days, 3 and 6 monthsin the main group (from 67.5[50.0;77.5] to 56.0[50.0;68.0] to 46.0[37.0;50.0] to 50.0[38.0;70.0] mm respectively). We obtained a significant(p<0.05) decrease in fat mass according to bioimpedanceometry in the main group after 14 days and 3 months, respectively (from65.7[49.2;72.1] to 60.9[42.2;66.7] to 55.3[39.3;62.2] kg, respectively). In group 1 the reduction in adipose tissue by air-substituted bodyplethysmography was also significantly (p<0.05) different after 14 days, 3 months respectively (from 56.8[41.3;77.5] to 49.7[40.1;57.1]to 44.4[34.4;64.4] kg). Body composition analysis data over time confirm the effectiveness of comprehensive programs in weight loss.Conclusion. A new comprehensive program including aerobic and strength training, kinesohydrotherapy and balance therapycombined with a low-calorie diet showed more significant effects on weight loss, reduction in the thickness of fatty folds and changesin body composition, including at long-term follow-up, than the standard method of rehabilitation.